Assessment of Direct RT-qPCR for SARS-CoV-2 Detection by Multiplexed Assay - Rachel Cruz Alves; José Henrique Franscisco Roma; Bruno Moreira Carneiro; Renata Dezengrini Slhessarenko; Juliana Helena Chavez Pavoni (Brazilian Archives of Biology and Technology)
Abstract RNA extraction is usually required for molecular detection methods. On the other hand, this step implies time consumption and additional cost to laboratorial routine. This study evaluated the use of direct-RT-qPCR for SARS-CoV-2 detection compared to the gold standard extraction method. An exploratory stage was performed using DMSO, glycerol, Tween 20 and Easy Extract® DNA-RNA addition in a pool of highly positive clinical samples (CT<25), which were subsequently tested by AllplexTM 2019-nCoV assay. Validation was performed with 54 SARS-CoV-2 positive and five negative clinical samples comparing three distinct conditions: (i) 1:1 water dilution, (ii) 1.5% DMSO dilution, or (iii) crude samples. Results of the exploratory stage showed Cycle Threshold (CT) values very close to those obtained by the reference extraction step in high viral load samples. However, when lower viral load samples were analyzed, a slight concordance was observed compared to the extraction step. In the validation stage, it was observed that water or 1.5% DMSO dilution presented 97.3% of concordance in samples with CT≤30, resulting in 97.4% of sensitivity and 0.83 Kappa coefficient. Sensitivity was reduced with samples CT>30 and with crude samples. The methodology showed reproducibility with differents operators. These results reinforce the good performance of direct RT-qPCR methods in active SARS-CoV-2 infection, allowed cost and time reduction of diagnosis.